Efeitos da amitriptilina na resposta inflamatória e proliferativa induzida por implante de esponja em camundongos - Karina Scheuermann (2021)
Amitriptyline (AM) is a drug used to treat several conditions that affect the central nervous system (CNS), and it has been shown to be effective in preventing and controlling pain, including those of inflammatory origin. In the literature, studies show that AM is also able to modulate inflammatory and proliferative processes (angiogenesis and fibrogenesis) in various pathological conditions. However, its effects on these processes in response to biomaterial implants have not yet been reported. In this work, we used a polyether-polyurethane matrix (subcutaneous implant) to evaluate the effects of AM treatment on the inflammatory and proliferative profile in fibrovascular tissue induced by the implant in C57BL/6 mice. The animals received for 7 days, once/day, 5mg/kg of AM (treated group) or filtered water (control group), by gavage, in two treatment protocols. In the first, treatment started on the day of surgery and the implants were removed 7 days after implantation. In the second, treatment started 7 days after implantation of the sponge and it was removed on the 14th day after implantation. The inflammatory markers evaluated, myeloperoxidase (MPO), nitrite (NO) content, levels of cytokines (IL-6, IFN-γ and TNF-α) and chemokines (CXCL1 and CCL2), activation of the transcription factor NF-κB (CT 1.22 ± 0.04; AM 0.72 ± 0.08), numbers of mast cells and foreign body giant cells were significantly reduced in the implants when treatment started 7 days after implantation (chronic inflammation). This reduction was also observed in vascular parameters VEGF and IL-1β, and in the number of blood vessels; as well as in the TGF-β fibrogenic parameters (local and systemic), in the deposition of collagen types I, III and total (CT 478315 ± 29013; AM 170143 ± 30072), and in the thickness of the fibrous capsule formed around the implant. In contrast, only MPO activity, mast cell number and NF-κB pathway activation decreased when treatment started on the day of implant placement (subacute inflammation). Considering that the implantation of biomaterials is a widely used therapeutic procedure, and that adverse responses to its implantation can compromise the functionality of the devices, our results suggest that amitriptyline has potential therapeutic value as an anti-inflammatory and antifibrogenic agent in long-term inflammatory pathological processes.